Pengaruh Kecemasan Matematika terhadap Pemahaman Konsep Matematika - Shinta Dwi Handayani (Universitas Indraprasta PGRI Jakarta, 2019)
The purpose of this research is to know the influence of math anxiety towards the understanding of mathematical concepts. Method the used research is survey and sample methods with the technique of simple random sampling, the sample in this study as 90 students. Analysis research to hypothesis testing using linear regression analysis test, with the results of a test of hypothesis generating, there is the influence of mathematics anxiety towards the understanding of mathematical concepts.